2004
DOI: 10.1097/00004728-200407000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Differentiating Human Coronary Plaque Morphology Using Contrast-Enhanced Multislice Spiral Computed Tomography

Abstract: The comparison with histopathology confirms that tissue density as determined by contrast-enhanced MDCT might be used to differentiate atherosclerotic plaque morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(91 citation statements)
references
References 18 publications
3
84
2
2
Order By: Relevance
“…6,7 While single slice computed tomography showed conflicting results in determining carotid plaque composition, MDCT showed good correlation of findings with histological analysis of coronary plaques. [23][24][25][26][27] Histological analysis of coronary plaques showed that remodeling of atherosclerotic plaque changes its histological content. Therefore, the period between imaging and histological analysis should be as short as possible.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 While single slice computed tomography showed conflicting results in determining carotid plaque composition, MDCT showed good correlation of findings with histological analysis of coronary plaques. [23][24][25][26][27] Histological analysis of coronary plaques showed that remodeling of atherosclerotic plaque changes its histological content. Therefore, the period between imaging and histological analysis should be as short as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the plaque was characterized by color coding based on CT value (HU). Referring to published studies (13)(14)(15), the software color codes of the non-calcified coronary plaque were classified into low attenuation plaque (0-50 HU), lipid-rich plaque, intermediate attenuation plaque (51-120 HU), fibrous plaque; and the volume of …”
Section: Discussionmentioning
confidence: 99%
“…The readers assessed 13 coronary segments from each patient according to a modified American Heart Association classification (right coronary artery = segments 1-4; left main = segment 5; left anterior descending coronary artery = segments 6-10; left circumflex artery = segments [11][12][13]. In accordance with the findings reported by Schroeder et al, 18 coronary soft plaques were defined as lesions in which the density was attenuated from that of the contrastenhanced vessel lumen (density <100 Hounsfield U (HU)). A preliminary study was carried out to examine the agreement between the visual assessment of density attenuation and decrease in HU based on gradation gray scale analysis of the MDCT images.…”
Section: Mdct Image Interpretationmentioning
confidence: 99%
“…15,16 Its reliability in the determination of coronary plaque morphology has been recently demonstrated by studies using IVUS and histopathologic studies. 17,18 The advantages of MDCT are that it is relatively noninvasive compared with intracoronary angioscopy and IVUS, and has sufficient stability for observation of the entire coronary tree. Indeed, at present, MDCT is thought to be 1 of the best methods of evaluating coronary plaque characteristics.…”
mentioning
confidence: 99%